Design of microstrip ultra wide band antenna with two notch filters for wireless communication - Abdulhasan, Raed Abdulkareem (2015)
This research develops a small size UWB patch antenna with two notch filters. U-shaped and J-shaped slots are loaded in the patch of the antenna for WiMAX and WLAN frequency band rejection. The antenna is simulated using the commercially available CST Microwave Studio software. The slots dimensions are systematically calculatedand optimized to achieve the desired band rejection responses. A multi-state reconfigurable UWB circular patch antenna with two notch filters. The two notch filters can be implemented using U-shaped and J-shaped slots embedded on the patch for WiMAX and WLAN frequency bands rejection. In order to add reconfigurable characteristics to the patch antenna, two copper strips are putted on the slots to represent the ON and OFF switching status of an ideal Pin diode. By using this simple switching technique, the current distribution of the patch changes and enables the antenna to have four modes of operation. The achieved results demonstrate that the antenna can function over the entire UWB working frequency range (3.1 GHz to 10.6 GHz) in one of the switching configurations. On the other hand, it rejects one or both WiMAX (3.13 – 3.7 GHz) and WLAN (5.15-5.85 GHz) frequency bands in the other three switching configurations. The antenna is simulated using electromagnetic simulation software CST Studio Suite. The obtained results were experimentally validated and good agreement was observed.